Precision health: A nursing perspective - Mei R. Fu; Emma Kurnat-Thoma; Angela Starkweather; Wendy A. Henderson; Ann K. Cashion; Janet K. Williams; Maria C. Katapodi; Karin Reuter-Rice; Kathleen T. Hickey; Veronica Barcelona de Mendoza; Kathleen Calzone; Yvette P. Conley; et al. (Elsevier, 2020)
Precision health refers to personalized healthcare based on a person's unique genetic, genomic, or omic composition within the context of lifestyle, social, economic, cultural and environmental influences to help individuals achieve well-being and optimal health. Precision health utilizes big data sets that combine omics (i.e. genomic sequence, protein, metabolite, and microbiome information) with clinical information and health outcomes to optimize disease diagnosis, treatment and prevention specific to each patient. Successful implementation of precision health requires interprofessional collaboration, community outreach efforts, and coordination of care, a mission that nurses are well-positioned to lead. Despite the surge of interest and attention to precision health, most nurses are not well-versed in precision health or its implications for the nursing profession. Based on a critical analysis of literature and expert opinions, this paper provides an overview of precision health and the importance of engaging the nursing profession for its implementation. Other topics reviewed in this paper include big data and omics, information science, integration of family health history in precision health, and nursing omics research in symptom science. The paper concludes with recommendations for nurse leaders in research, education, clinical practice, nursing administration and policy settings for which to develop strategic plans to implement precision health. Keywords: Nurses, Genomics, Omics, Precision medicine, Precision health